Violence Against Healthcare Workers by Mentally Ill Patients: Impact on Staff in Dementia Wards at Julian Hospital, Norwich - Ruzaika Jaufer; Amal Baby; Minfas Affan (BJPsych Open, 2025)
Aims: This study aims to explore the risk factors, impact, and support systems related to violence against healthcare staff by mentally ill patients. It examines the psychological, physical, and professional effects on staff, while assessing the effectiveness of current reporting mechanisms. Addressing the global issue of underreporting violence against healthcare staff, the study seeks to raise awareness, promote safety, and advocate for stronger preventative measures.